Hybrid piezoelectric-electromagnetic energy harvester using a nonlinear curved T-shaped beam for broadband applications - Mohammad Farhan (17017683) (2025)
This work investigates the performance of a novel hybrid piezo-electromagnetic energy harvester integrated with curved T-shaped and straight beams for efficient broadband vibration energy harvesting (VEH). The proposed system leverages the synergy between piezoelectric and electromagnetic transduction mechanisms while utilizing the unique dynamic properties of curved beams and magnetic nonlinearity to enhance energy harvesting efficiency across a wide frequency range. The developed hybrid harvester consists of two curved T-shaped beams with three piezoelectric patches and two straight cantilevers with one patch on each, with a magnet as a variable tip mass. Simulations were conducted to analyze stress distribution, modal behavior, and harmonic response under various vibrational conditions for T-shaped and curved T-shaped beams. The prototype was tested using a shaker and DAQ device for four different configurations of tip magnets with increasing mass and electromagnetic field density. The average voltage of 27.81 V for piezoelectric with average output power of 0.773 mW as well as energy density of 0.0101 Wm −3 , and 0.014 V with average power output of 0.736 nW from electromagnetic energy harvester at 1 MΩ external load for the tip mass configuration M4 within the frequency range of 1–150 Hz was achieved. In contrast, the overall average voltage generated at M1, M2, and M3 configurations is 5.38, 9.78, and 15.25 V, respectively. The frequency average voltage (FAV) was calculated for all configurations of M1, M2, M3, and M4 as 6.19, 8.25, 9.94, and 11.37 V/Hz. The findings reveal that the hybrid piezo-electromagnetic energy harvester can effectively harvest energy from broadband vibrational sources, making it a promising solution for powering wireless sensors, wearable electronics, and other low-power devices in applications such as structural health monitoring, industrial automation, and smart infrastructure. Other Information Published in: Journal of Vibration and Control License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/10775463251370572